If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + 7) = 75 Reorder the terms: 3(7 + k) = 75 (7 * 3 + k * 3) = 75 (21 + 3k) = 75 Solving 21 + 3k = 75 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3k = 75 + -21 Combine like terms: 21 + -21 = 0 0 + 3k = 75 + -21 3k = 75 + -21 Combine like terms: 75 + -21 = 54 3k = 54 Divide each side by '3'. k = 18 Simplifying k = 18
| x^5+2x^2=0 | | 5a+2(3a+4)-2a= | | 2b^2-3b=5 | | N=55000-2000x | | 7v-5=4v+4 | | 3(v+4)+v=20 | | 5x-5+6-3x=0 | | q*4q*5q= | | 5(2y+10)=110 | | 3x+2y-z=23 | | 3-5x=4+2x | | X^4-3x^2-x^3+4x-4=0 | | x=6.25+0.25y+-0.5z | | 5(x+6)+2=37 | | 3(x+1)-x+4=2x+8 | | 282-10x=20x+12 | | z^3-i*z^2+4z-4i=0 | | x^4-7x^3+7x^2+42x+63=0 | | 4(x+12)+2(x+18)=-6 | | x^4+11x^3+7x^2+42x+63=0 | | x^4+6x^3+7x^2+42x+63=0 | | (5-x)*(6x+2)+5=0 | | 2*x^2+4=0 | | 4(x+2)-3(x+1)=3 | | (5-x)*(6x+2)=5 | | x^4+6x^3-7x^2-42x-63=0 | | 2(3x-1)-4(2x+5)=-5 | | 7x-5=2b+15 | | 3x+2y-z=28 | | 3(4k-11)=75 | | 4*(12-6y)+2y=-7 | | 4(5-x)+2x-10=-2x+10 |